Malawi : Debt Relief at the Heavily Indebted Poor Countries Initiative Completion Point and Under the Multilateral Debt Relief Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Malawi has made satisfactory progress in implementing its Poverty Reduction Strategy Paper (PRSP) for at least one year, and maintained satisfactory macroeconomic policies as evidenced by its performance under a program supported by the Poverty Reduction and Growth Facility (PRGF) over the last fiscal year 2005/2006. The completion point analysis shows the actual outturn to be 245 percent of exports. After additional voluntary bilateral debt relief, this ratio declines to 229 percent of exports. The paper assesses the sensitivity of debt indicators to changes in key economic variables.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet